Science Student Teachers' Beliefs about the Nature of Science and its relation to their Perception of Science Laboratory Environment - Abdullah Ambusaidi; Ali Al-Shuaili (Sultan Qaboos University, 2010)
This study aimed at investigating the science student teachers' beliefs about the nature of science and its relation to their perception of the science laboratory environment. Two instruments were used: a scale for beliefs about the Nature of Science and a Laboratory Environment Inventory. The instruments were administered to 61 students enrolled in the College of Education (Science Education) in the year 2008/2009. The findings revealed that students' strength of beliefs regarding the nature of science dimensions was in this descending order: Observation and Inference, Theories and Laws Relationships, Tentative, Social and Cultural Impact, Empirical Basis, Creativity and Human Imagination. On the other hand, students' strength of perception regarding the science laboratory environment domains was in this descending order: Materials and Equipment, Clear Information, Integration between Theory and Practice, Students-Students and Students-Mentors interactions, open-ended tasks. Besides, there was a low to moderate correlation between some of the beliefs about Nature of Science Dimensions and Science Laboratory Environment Domains.